Sentinel lymph node biopsy by transvaginal natural orifice transluminal endoscopic surgery for early-stage endometrial cancer: a systematic literature review - Wernly, Déborah; Nef, James; Huber, Daniela (Frontiers in Surgery, 2025)
IntroductionSentinel lymph node (SLN) mapping has become a standard approach for early-stage endometrial malignancies, offering reduced morbidity compared to complete lymphadenectomy. Recently, transvaginal natural orifice transluminal endoscopic surgery (vNOTES) has emerged as a novel minimally invasive technique for SLN biopsy, with potential benefits in early surgical outcomes. This systematic review evaluates current evidence on SLN biopsy performed via vNOTES.Material and methodsA systematic literature search was conducted in PubMed, Embase, and Web of Science for articles published between January 1, 2014 and January 31, 2025. Studies were included if they reported SLN biopsy by vNOTES in at least 10 patients with early-stage endometrial cancer and provided detailed data on SLN detection. Our primary outcomes focused on SLN detection and failure rates. Secondary objectives included the early operative outcomes. PROSPERO registration number was CRD42024612607.ResultsSeven studies comprising 231 patients were included. The overall bilateral SLN detection rate was 89.2%, with higher detection in the retroperitoneal subgroup (94.3%) compared to the transperitoneal subgroup (81.1%). The overall failure rate was 3.9%. Nodal metastases were reported in 5.6% (10/179) of patients. Intraoperative complications occurred in 4.8% of cases, with bladder injury being the most frequent. The conversion rate to laparoscopy was 6.5%, primarily due to unsuccessful SLN mapping. Postoperative complications occurred in 3% of patients and were mostly minor. Comparisons with conventional laparoscopy showed similar operative times and blood loss, while vNOTES appeared to offer potential advantages in reducing pain and shortening hospital stay.ConclusionvNOTES is a promising technique for SLN mapping in early-stage endometrial cancer, demonstrating high detection rates with low complication rates. However, evidence remains limited and heterogeneous, highlighting the need for larger, prospective, and randomized studies to validate long-term oncological safety and define its role in clinical practice.